PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DI RUMAH MAKAN “LESEHAN 88” MADIUN - Dian kristiana (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2014)
This study aims to determine the quality of the product at home eating "Lesehan 88" Madiun, to determine customer satisfaction in restaurants "Lesehan 88" Madiun, and to know is there any effect of product quality on customer satisfaction in the eating "Lesehan 88" Madiun.The samples in this study using a quota sample of 100 people, based on the characteristics of customers who have made a purchase at least once. Data collection using questionnaires and documentation. In analyzing the data used statistical method to test the product moment correlation is valid whether or not the instruments used and the method of regression tests for testing the hypothesis put forward in this study.The results showed that the quality of products have an influence a positive relationship to customer satisfaction in the eating "Lesehan 88" Madiun. It is derived from the value of 0.752 while the value rhitung rtabel 0.195 (0.752 ≥ 0.195). On the other hand Sighit value of 0.000 and the value Sigprob at 00:05 (0.000 ≤ 0.05) with the Ha acceptable means quality products have a relationship with customer satisfaction in restaurants "Lesehan 88" Madiun. It also obtained the F test value, while the value Fcount Ftable 3.938 127.623 (127.623 ≥ 3.938). On the other hand Sigprob Sighit of 0.000 and 0.05 (0.05 ≤ 0.000). It means that there is rejection of H0 which indicates that there are significant between product quality to customer satisfaction in the eating "Lesehan 88" Madiun. Also obtained regression coefficients (t test) with tcount 11.297 1.660 while the value ttable (≥ 11.297 1.660). On the other hand sighit value of 0.000 and Sigprob value of 0.05 (0.05 ≤ 0.000). By this means Ha received no difference between the effect of product quality on customer satisfaction in the restaurant "Lesehan 88" Madiun. R2 of 0,566, results showed that 56.6% of customer satisfaction variables quality of the product, while the remaining 43.4% is influenced by other factors not examined.